Strategic planning and change management.Examples of Barcelona, Seville and Saragossa (Spain) - González González, María Jesús; López González, Alejandro (Bulletin of Geography. Socio-economic Series, 2015)
This work attempts to underline that motivating and managing change in the mentality of its environment, and being in tune with society’s changing needs is the basis of successful strategic planning. Our aim is to highlight planning as a way of learning, that is, planning implies changing ways of thinking, not making plans. Strategic learning requires releasing the mind in order to slip flexibly into the continuous line and to achieve the creation of possible action courses from a fertile dialogue between thought and action. Using our insights from the two literatures, we propose a dynamic, integrative conceptual model of change based on organizational learning. This practice has been analysed in three Spanish cities where important events have taken place.